Enhancing surimi structure by lycopene-fennel extract Pickering emulsion: application in 3D printing analog beef with dynamic color and flavor retention - Juncheng Zhu; Hongjie Dai; Chunlin Yuan; Shujin Tang; Liang Ma; Xiaoyi Tan; Hongxia Wang; Yuhao Zhang (Food Research International, 2026)

Residual dissipation, processing factor and risk assessment of three pesticides in peaches from field to juice processing - Zehui Liu; Yujiao Wang; Dianying Men; Lin Ma; Guangyue Wen; Shaoxiang Fei; Hongxia Tang; Yanna Han; Maofeng Dong; Li Zhao (Food Control, 2026)

Enhancing large-scale streamflow prediction by coupling structural inductive bias with meta-learning - Xuan Tang; Yuting Zhao; Yuan Yu; MingRui Yu; Guanghua Qin; Hongxia Li (Journal of Hydrology, 2026)

Development of a hydrazinolysis method for the determination of vinclozolin in foods by SPE and GC–MS/MS - Hongxia Tang; Yubo Li; Qinyi Sheng; Rui Yu; Dongwei Wang; Lin Ma; Guangyue Wen; Maofeng Dong; Xianbin Li; Li Zhao (Food Chemistry, 2026)

Deubiquitinase USP22 maintains B cell homeostasis through the CHD4-CD19 signaling axis and is dysregulated in Kawasaki disease - Yanmei Huang; Pengyue Gao; Siyu Zhao; Juan Lai; Xin Zhang; Weijiayi Wang; Hongxia Tang; Fei Guan; Xi Luo; Xin Dai; Heather Miller; Lu Yang; et al. (Science Bulletin, 2026)

Networked power infrastructure, energy transition, and supply chain resilience: Evidence from China's ultra-high voltage transmission - Ziru Tang; Zenglian Zhang; Zhiyuan Dong; Hongxia Wang (Journal of Environmental Management, 2026)

Spherical silica-alumina with mixed acid structure for effective catalysis of the ketalization of glycerol with acetone - Hongxia Wang; Yiwang Tang; Yuqing Cheng; Xintong Liu; Gang Yu; Xiulan Xin (Biomass and Bioenergy, 2026)

High-sensitivity Temperature Sensing via Color Change: A Study on the Thermal Coupling and Non-thermal Coupling Energy Levels in YVO4:Tm3+/Er3+ - Zhensheng Lu; Hongxia Tang; Meilin Song; Changxing Yu; Changwen Wang (Journal of Fluorescence, 2026)

Liquid-phase microextraction assisted surface-enhanced Raman spectroscopy: On-site quantification of amphetamine-type stimulants in complex samples from crime scenes - Tongfei Gao; Zhuangzhuang Dong; Jianhua Xiong; Hongxia Hao; Xiantao Shen; Wenge Tang; Zhen Tong; Chuixiu Huang (Analytica Chimica Acta, 2026)

A novel recombinant serotype 4 fowl adenovirus efficiently protects both serotype 4 and 11 fowl adenovirus - Shi Liu; Ye Tang; Tuofan Li; Zhimin Wan; Hongxia Shao; Aijian Qin; Quan Xie; Wei Gao; Jianqiang Ye (Veterinary Microbiology, 2025)

Dual-responsive carboxymethyl cellulose-based hydrogel sensor with antibacterial activity for wound monitoring and infected wound repair - Zhengjie Yu; Fanwei Zeng; Yuejin Cai; Zijie Wang; Ze Chen; Ruizi Wang; Qingfeng Sun; Xiaodong Tang; Xiaoping Shen; Hongxia Xie (Chemical Engineering Journal, 2025)

The high-affinity K+ transporter IbHAK5 enhances potassium ion absorption and improves root morphology in sweetpotato (Ipomoea batatas) - Rong Jin; Peng Zhao; Mengxiao Yan; Ming Liu; Weijuan Fan; Qiangqiang Zhang; Xiaoya Zhu; Jing Wang; Yongchao Yu; Jun Yang; Hongxia Wang; Zhonghou Tang (Transgenic Research, 2025)

Zinc Ameliorates LPS-Induced Depressive-Like Behaviors Via Modulating Microglial Polarization - ChenQi Li; Gen Miao; Wenjing Shi; Yangjuan Gu; Weiwei Li; Mengyu Cai; Yicui Qu; Yuxiao Tang; Hongtao Lu; Hongxia Li; Hui Shen (Biological Trace Element Research, 2025)

Causality-Guided Deep learning for streamflow predicting in a mountainous region - Xuan Tang; Guanghua Qin; Xuemei Wu; Yuting Zhao; Hongxia Li (Journal of Hydrology, 2025)

A versatile biosensor for detecting Zn2 + and Cu2+ in Alzheimer's disease cells and acidic foods via RNA G-quadruplex hydrolysis - Dawei Yang; Hongxia Sun; Ranran Sun; Haoyuan Feng; Ruiyang Bai; Qian Li; Li Yao; Yalin Tang (Journal of Hazardous Materials, 2025)

Standard observation plane annotation for diagnosis of ossicular chain in the temporal bone CT images - Xiaoguang Li; Tao Wang; Ruowei Tang; Hongxia Yin; Pengfei Zhao; Li Zhuo; Zhenchang Wang (Medical & Biological Engineering & Computing, 2025)

Insulin level regulators may affect cognitive ability caused by motion sickness: an experimental study - Mengyu Zhong; Jian Zhu; Bohan Zhang; Hui Shen; Hongxia Li; Yuxiao Tang; Shuang Nie; Fengfeng Mo (Metabolic Brain Disease, 2025)

Algicidal activity and mechanism of novel Bacillamide a derivative against red tide algae Skeletonema costatum and Prorocentrum minimum - Huili Li; Xiaoxue Li; Yi Liu; Ronglian Xing; Hongxia Zhang; Wenguang Jia; Lihong Chen; Rui Li; Zhen Yu; Zhihong Tang (Pesticide Biochemistry and Physiology, 2025)

Prevalence of malnutrition among adult inpatients in China: a nationwide cross-sectional study - Yan Liu; Chunhua Song; Xue Wang; Xianghua Ma; Pianhong Zhang; Gaiyun Chen; Zhenqian Cheng; Juying Liu; Ying Yao; Wenjun Ma; Zengning Li; Ping Sun; et al. (Science China Life Sciences, 2025)

Three birds with one stone: Sewage sludge deep-drying in 1 hour using secondary aluminum ash to fabricate bricks - Xianghai Kong; Yanping Zhu; He Xu; Jinghong Ye; Shuang Wang; Heliang Xu; Rongjun Zhang; Hongxia Tang; Dongfang Wang; Dongqing Cai (Water Research, 2024)

A supramolecular fluorescence probe that simultaneously responds to viscosity and G-quadruplex for autophagy detection - Ruiyang Bai; Dawei Yang; Ranran Sun; Xiufeng Zhang; Lei Shi; Jing Liu; Hongxia Sun; Li Yao; Yalin Tang (Analytica Chimica Acta, 2024)

Modulating the stability and gastrointestinal tolerance of lycopene in low-oil gelatin emulsions by constructing cellulose network barrier - Xin Feng; Hankun Zhu; Hongjie Dai; Yong Yu; Hongxia Tan; Mi Tang; Kangting Sun; Yapeng Lu; Yugang Liu; Liang Ma; Yuhao Zhang (Food Hydrocolloids, 2024)

Polydopamine-assisted minute fabrication of vertically aligned ZIF-L membranes for CO2/N2 separations - Keming Zhang; Sihui Li; Xiaohe Tian; Rui Zhang; Xiaoting Feng; Qingnan Wang; Yanting Tang; Chenlu Liu; Hongxia Gao; Shaofei Wang (Chemical Engineering Journal, 2024)

Improved Streamflow Simulation by Assimilating In Situ Soil Moisture in Lumped and Distributed Approaches of a Hydrological Model in a Headwater Catchment - Hongxia Li; Yuanyuan Huang; Yongliang Qi; Yanjia Jiang; Xuan Tang; Elizabeth W. Boyer; Carlos R. Mello; Ping Lan; Li Guo (Water Resources Management, 2024)

Regulation of three novel pepper thiothiazolidinones on the fecundity of Spodoptera frugiperda - Bin Tang; Ye Han; Qixuan Mao; Haoyu Fu; Yujia Luo; Liyuhan Hua; Busheng Liu; Gao Hu; Shigui Wang; Nicolas Desneux; Hongxia Duan; Yan Wu (Pesticide Biochemistry and Physiology, 2024)

Transcriptomic analysis of hydrogen peroxide-induced liver dysfunction in Cyprinus carpio: Insights into protein synthesis and metabolism - Wenrong Feng; Yuanfeng Xu; Shengyan Su; Fan Yu; Jianlin Li; Rui Jia; Changyou Song; Hongxia Li; Pao Xu; Yongkai Tang (Science of The Total Environment, 2024)

Moso bamboo (Phyllostachys edulis) expansion enhances soil pH and alters soil nutrients and microbial communities - Yaoxing Wu; Jiahuan Guo; Zhiying Tang; Tianxiang Wang; Wenting Li; Xiaorong Wang; Hongxia Cui; Xingyi Hu; Lianghua Qi (Science of The Total Environment, 2024)

Isolation, heterologous expression, and functional determination of an iron regulated transporter (IRT) gene involved in Fe2+ transport and tolerance to Fe2+ deficiency in Vitis vinifera - Zhizhong Song; Xue Wang; Mengyuan Li; Youzheng Ning; Shengpeng Shi; Guangrong Yang; Hongxia Zhang; Meiling Tang; Bin Peng (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)
In plants, iron (Fe) regulated transporters (IRT) play important roles in uptake and transport of Fe that contributes to plant growth and development. However, biological functions of IRT transporters in fruit trees are still unknown. This study isolated 10 VvIRT genes from ‘Marselan’ grape, with varying expression levels across different tissues/organs, particularly enhanced under Fe depletion, especially in roots. Notably, VvIRT7 is the most abundantly expressed IRT gene in grape, beneficially restoring the Fe 2+ uptake defect of yeast mutant DEY1453. Furthermore, VvIRT7 showed dominant expression in the roots of irt1 /35S:: IRT7 complementation lines. Overexpressing of VvIRT7 rescued the retarded growth of irt1 knockout mutant, by increasing the fresh weight, dry weight, total root length, total root surface, lateral root numbers, total leaf chlorophyll, ACO activity, NiR activity, SDH activity, and tissue Fe concentration. This study provides insights for understanding molecular mechanisms of Fe uptake and transport in grape.

Dual-responsive fluorescence probe for measuring HSO3− and viscosity and its application in living cells and real foods - Xiaoying Ma; Xiufeng Zhang; Buyue Zhang; Dawei Yang; Hongxia Sun; Yalin Tang; Lei Shi (Food Chemistry, 2024)

Residue behaviors, degradation, processing factors, and risk assessment of pesticides in citrus from field to product processing - Hongxia Tang; Qiang Sun; Jiaqing Huang; Guangyue Wen; Lijun Han; Lei Wang; Ying Zhang; Maofeng Dong; Weimin Wang (Science of The Total Environment, 2023)

Punicalagin alleviates the hyperproliferation of keratinocytes in psoriasis through inhibiting SKP2 expression - Lipeng Tang; Bowen Zhang; Guanzhuo Li; Ying Zhu; Bing Feng; Zuqing Su; Wenhui Han; Huilin Huang; Qiuping Li; Maojie Wang; Yuchao Chen; Huazhen Liu; et al. (Journal of Natural Medicines, 2023)

Improvement of low-oil gelatin emulsions performance by adjusting the electrostatic interaction between gelatin and nanocellulose with different morphologies - Xin Feng; Hongjie Dai; Hongxia Tan; Mi Tang; Liang Ma; Yuhao Zhang (Food Hydrocolloids, 2023)

Insights into biodegradation behaviors of methanolic wastewater in up-flow anaerobic sludge bed (UASB) reactor coupled with in-situ bioelectrocatalysis - Yijing Gao; Teng Cai; Jian Yin; Huan Li; Xinyu Liu; Xueqin Lu; Hongxia Tang; Weijie Hu; Guangyin Zhen (Bioresource Technology, 2023)

Characterization of RING-type ubiquitin SINA E3 ligases and their responsive expression to salt and osmotic stresses in Brassica napus - Fengyan Fang; Wenlong Zhou; Yanfeng Liu; Zhizhong Song; Songfeng Zheng; Fei Wang; Zeyu Lu; Dazhuang Qi; Bei Li; Nan Sun; Xiaoli Tang; Juan Zhang; et al. (Plant Cell Reports, 2023)

An EMD–PSO–LSSVM Hybrid Model for Significant Wave Height Prediction - Gang Tang; Jingyu Zhang; Jinman Lei; Haohao Du; Hongxia Luo; Yide Wang; Yuehua Ding (Journal of Marine Science and Engineering, 2023)
The accurate prediction of significant wave height (SWH) offers major safety improvements for coastal and ocean engineering applications. However, the significant wave height phenomenon is nonlinear and nonstationary, which makes any prediction work a non-straightforward task. The aim of the research presented in this paper is to improve the predicted significant wave height via a hybrid algorithm. Firstly, an empirical mode decomposition (EMD) is used to preprocess nonlinear data, which are decomposed into several elementary signals. Then, a least squares support vector machine (LSSVM) with nonlinear learning ability is adopted to predict the SWH, and a particle swarm optimization (PSO) automatically performs the parameter selection of the LSSVM modeling. The results show that the EMD–PSO–LSSVM model can compensate for the lag in the prediction timing of the prediction models. Furthermore, the prediction performance of the hybrid model has been greatly improved in the deep-sea area; the prediction accuracy of the coefficient of determination (R2) increases from 0.991, 0.982, and 0.959 to 0.993, 0.987, and 0.965, respectively. The prediction performance results show that the proposed EMD–PSO–LSSVM performs better than the EMD–LSSVM and LSSVM models. Therefore, the EMD–PSO–LSSVM model provides a valuable solution for the prediction of SWH.

High temperature induced stable gelatin-gardenia blue system with hyperchromic effect and its food application in 2D writing/printing and 3D printing - Hongxia Wang; Yang Cheng; Juncheng Zhu; Zhiying Ouyang; Mi Tang; Liang Ma; Yuhao Zhang (Food Chemistry, 2023)

Genome-wide analysis of growth-regulating factor genes in grape (Vitis vinifera L.): identification, characterization and their responsive expression to osmotic stress - Qiang Hu; Binyu Jiang; Liru Wang; Yanjing Song; Xiaoli Tang; Yanhong Zhao; Xiaobin Fan; Yafeng Gu; Qiuling Zheng; Jieshan Cheng; Hongxia Zhang (Plant Cell Reports, 2023)

Impact of biochar on red paddy soil physical and hydraulic properties and rice yield over 3 years - Can Chen; Hongxia Zhu; Qing Lv; Qian Tang (Journal of Soils and Sediments, 2022)

Halomonas salipaludis sp. nov., isolated from a saline-alkali wetland soil - Juyuan Xing; Qi Gong; Liu Tang; Jiao Li; Hua Fan; Xiaowei Wang; Hongxia Liu; Guishan Zhang; Jinxing Zhu (Archives of Microbiology, 2021)

Identification, expression and enzyme activity of the group III sPLA 2 s in Cyprinus carpio L - Yuxin Xu; Hongxia Li; Dihui Xu; Jianlin Li; Fan Yu; Meiyao Wang; Qin Wang; Yunsheng Wu; Qiyuan Zhang; Yongkai Tang; Juhua Yu (Journal of Fish Biology, 2021)
Five group III secreted phospholipase (pla2g3s) homologous genes located on different linkage groups were identified from common carp ( Cyprinus carpio ), which we named Ccpla2g3a1 , Ccpla2g3a2 , Ccpla2g3b , Ccpla2g3c1 and Ccpla2g3c2 . The five genes encode 530, 525, 461, 752 and 753 amino acids, respectively. Sequence analysis showed that the Ccpla2g3a s contain seven exons and the others contain four exons. Synteny analysis of fish pla2g3s indicated that pla2g3a and pla2g3b were from the same ancestor gene, and Ccpla2g3a 1, Ccpla2g3a 2, Ccpla2g3c 1 and Ccpla2g3c 2 were from the specific genome duplication of common carp. Due to the significant variation of the pla2g3bs from common carp and zebrafish ( Danio rerio ), they formed a separate group in the phylogenetic tree. The tissue distributions of Ccpla2g3 s coincided with their expression profiles during the embryo stages. The expression levels of Ccpla2g3a s and Ccpla2g3c s were low at the embryo stages, and they were abundant in the liver and brain, respectively, whereas the expression of Ccpla2g3b was high at 0.5 h after fertilization and in the ovary. We obtained three soluble recombinant proteins of the bee venom‐like PLA2 (BVLP) from Ccpla2g3 and evaluated their PLA 2 enzyme properties. The optimum pHs of MBP‐a1‐BVLP, MBP‐b‐BVLP and MBP‐c1‐BVLP were 7.5, 7.0 and 8.0, respectively, and specific activities were 7.68 ± 0.66, 4.155 ± 0.158 and 1.93 ± 0.05 U μmol –1 , respectively. The K d for Ca 2+ of MBP‐b‐BVLP was the lowest (2.6 μM), whereas the values for both MBP‐a1‐BVLP and MBP‐c1‐BVLP were about 15 μM. The K m values of three proteins ranged from 31.9 to 41.91 μM.

Influence of Dose on Neutrophil-Mediated Delivery of Nanoparticles for Tumor-Targeting Therapy Strategies - Min Liu; Cong Li; NaYan; Dan Zhao; Hongxia Zhang; Jie Li; Xueying Tang; Xinrong Liu; Yihui Deng; Yanzhi Song (AAPS PharmSciTech, 2021)

Dorsolateral Striatal proBDNF Improves Reversal Learning by Enhancing Coordination of Neural Activity in Rats - Wei Sun; Hongxia Che; Jia Li; Dongxin Tang; Xiaoyun Liu; Wenhui Liu; Lei An (Molecular Neurobiology, 2020)

Ectopic expression of LoSVP, a MADS-domain transcription factor from lily, leads to delayed flowering in transgenic Arabidopsis - Xiaoli Tang; Meixia Liang; Junjie Han; Jieshan Cheng; Hongxia Zhang; Xiaohua Liu (Plant Cell Reports, 2020)

Prior contact of Pinus tabulaeformis with ectomycorrhizal fungi increases plant growth and survival from damping-off - Haoqiang Zhang; Hongxia Yu; Ming Tang (New Forests, 2017)

Genome-wide identification of SAUR genes in watermelon (Citrullus lanatus) - Na Zhang; Xing Huang; Yaning Bao; Bo Wang; Hongxia Zeng; Weishun Cheng; Mi Tang; Yuhua Li; Jian Ren; Yuhong Sun (Physiology and Molecular Biology of Plants, 2017)

A serine protease inhibitor from Musca domestica larva exhibits inhibitory activity against elastase and chymotrypsin - Yan Tang; Ying Wang; Zhihuan Pei; Wenting Li; Dandan Zhang; Lei Liu; Lingcong Kong; Shuming Liu; Xiuyun Jiang; Hongxia Ma (Biotechnology Letters, 2016)

Dissipation kinetics and degradation mechanism of amicarbazone in soil revealed by a reliable LC-MS/MS method - Maofeng Dong; Wei Han; Emmanuel Njumbe Ediage; Liangxiu Fan; Hongxia Tang; Weimin Wang; Lijun Han; Zhihui Zhao; Weiguo Song; Zheng Han (Environmental Science and Pollution Research, 2015)

Characterization and expression analysis of two distinct neuropeptide Ya paralogues in Jian carp (Cyprinus carpio var. Jian) - Yongkai Tang; Hongxia Li; Jianlin Li; Fan Yu; Juhua Yu (Fish Physiology and Biochemistry, 2014)

Recombination in human coxsackievirus B5 strains that caused an outbreak of viral encephalitis in Henan, China - Hongxia Ma; Xueyong Huang; Kai Kang; Xingle Li; Xiaoyan Tang; Yunhui Ren; Youchun Wang; Guirang Zhao; Bianli Xu (Archives of Virology, 2013)

Growth performance of the clam, Meretrix meretrix, breeding-selection populations cultured in different conditions - Chao Wang; Xueliang Chai; Hongxia Wang; Baojun Tang; Baozhong Liu (Acta Oceanologica Sinica, 2013)

A TFIIIA-type zinc finger protein confers multiple abiotic stress tolerances in transgenic rice (Oryza sativa L.) - Ji Huang; Shujing Sun; Dongqing Xu; Hongxia Lan; Hui Sun; Zhoufei Wang; Yongmei Bao; Jianfei Wang; Haijuan Tang; Hongsheng Zhang (Plant Molecular Biology, 2012)

An efficient Agrobacterium-mediated transformation and regeneration system for leaf explants of two elite aspen hybrid clones Populus alba × P. berolinensis and Populus davidiana × P. bolleana - Haihai Wang; Cuiting Wang; Hua Liu; Renjie Tang; Hongxia Zhang (Plant Cell Reports, 2011)

Enhancement of stress tolerance in transgenic tobacco plants constitutively expressing AtIpk2β, an inositol polyphosphate 6-/3-kinase from Arabidopsis thaliana - Lei Yang; Renjie Tang; Jinqi Zhu; Hua Liu; Bernd Mueller-Roeber; Huijun Xia; Hongxia Zhang (Plant Molecular Biology, 2008)

New life cycles of Porphyra katadae var. hemiphylla in culture - Xiaorong Tang; Hongxia Jiang; Xiugeng Fei; Charles Yarish (Journal of Applied Phycology, 2004)